The global shipbuilding war: An in-depth analysis of the technological upgrading and competitive strategies of Major Global Regional Blocs - Sanusi Mohammed Sadiq; Invinder Paul Singh; Muhammad Makarfi Ahmad; Bashir Sanyinna Sani (Universitas Malikussaleh, 2026)
This study provides a comprehensive, longitudinal analysis of ocean goods trade dynamics for BRICS, the European Union (EU), G-20, G-77, and the OECD from 2012 to 2023. Utilizing data from UNCTAD, the research employs a tripartite analytical framework, examining Revealed Comparative Advantage (RCA), Trade Openness, and Trade Intensity indices across five key sectors: Marine Fisheries, Seafood Processing, Sea Minerals, Ships & Port Equipment, and High-Technology Manufactures. A critical methodological innovation involves adjusting nominal values for inflation to derive real-term trade metrics, revealing more accurate growth trajectories. The results unveil a complex, multi-polar ocean economy with distinct bloc specializations. BRICS demonstrates a robust and rising comparative advantage in shipbuilding, positioning it as a specialized industrializer, though its overall trade openness has declined in real terms. The synthesis of these findings leads to a novel typology of regional blocs within the global ocean economy. The discussion underscores the strategic implications of these divergent pathways, emphasizing the need for policies that align economic competitiveness with the principles of the sustainable Blue Economy. This study concludes that understanding these comparative dynamics is essential for crafting effective trade, industrial, and environmental policies aimed at fostering equitable and sustainable growth within the global ocean commons. Keywords: Blue Economy, Development; Economic Blocs; Sustainability; Supply Chain